KAJIAN MORFOLOGI DERIVASIONAL DAN INFLEKSIONAL DALAM BAHASA INDONESIA - Purnanto, Dwi (Kajian Linguistik dan Sastra, 2006)
This article deals with the study of words in the scope of morphology with the stress on Hockettâs ideas (1954) of Item and Arrangement (IA), Item and Process (IP), dan Word and Paradigm (WP). Using this approach, men to concern will really understand that derivational (or lexical) morphology studies words forma- tion resulted in new categories of the words while in inflectional morphology, such a result is not found. Inflectional morphology; on the other hand, deals with the result of words formation derived from the same lexems. The outstanding inference shows that to be the scope of word formation is only the derivasional morphology instead of inflectional one. The understanding of inflection becomes the scope of syntax since it is only completing the forms of lexem; however, derivation is in- cluded in lexicon for it provides new lexems.Â Key words: derivasional, infleksional, IA, IP, WP, word formation, and lexem.